Alternative fuels for decarbonisation of road transport sector in India: Options, present status, opportunities, and challenges. (1st December 2021) - Nouni, M.R.; Jha, Prakash; Sarkhel, Rudranath; Banerjee, Chandan; Tripathi, Arun K.; Manna, Joydev
Highlights: India's road transport sector heavily dependent on imported fossil fuels. Consequently, energy security, economy and environment are adversely impacted. Biofuels, CNG, CBG, LPG, methanol, electricity, and hydrogen are preferred alternative options. Policy supports for development of these alternative fuels are discussed. Opportunities and challenges for growth of these fuels are also analysed. Abstract: Rapid economic development and increasing population are contributing to growing energy demand in India. Road transport sector, almost fully dependent on petroleum oil, is the third highest user of the total final energy in India. More than four-fifth of crude petroleum is imported, which is responsible for nearly one-fifth of country's import bill. India's share of the global energy related CO2 emissions was about 7% in 2018, of which about 13% was caused by the transport sector. With a view of decarbonising the road transport sector and also addressing issues concerning energy efficiency, energy security, air quality and transport induced noise, alternative fuels have been explored in India for about two decades. This paper reviews policy support and related developments regarding biofuels, compressed natural gas, methanol, electricity, and hydrogen for automotive applications in India with a brief mention about international progress. The opportunities for their growth by 2030 and challenges to realise the potential are also analysed. Biofuels and electricity can offer significant opportunities for decarbonising the road transport sector in the near term. Compressed natural gas in short term and hydrogen in medium and long term may also play important roles in this regard.